2015
DOI: 10.1021/acs.jpcc.5b04103
|View full text |Cite
|
Sign up to set email alerts
|

Excess Electrons and Interstitial Li Atoms in TiO2 Anatase: Properties of the (101) Interface

Abstract: Lithium intercalation across the anatase (101) surface is investigated with hybrid DFT. It is demonstrated that the upper surface layers of the oxide are geometrically less constrained, allowing stabilization of both excess electrons (by 5 × 10 −2 eV) and intercalated Li + cations (by 1.1 × 10 −1 ) eV compared to bulk anatase. Li + ions tend to segregate in the first subsurface layers, forming rows along the [010] crystal direction. Also, excess electrons localize preferentially subsurface, as confirmed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 60 publications
3
17
0
Order By: Relevance
“…Recently, many researchers found that lithium (Li) doping plays an important role in the inhibition of activity in the TiO 2 network acting as an electron trapping or hole trapping [239][240][241]. Bouattour et al reported Li-doped TiO 2 nanoparticles through a sol-gel process and investigated their potential application as a photocatalyst for degradation of different organic compounds [240].…”
Section: Other Metal Dopantsmentioning
confidence: 99%
“…Recently, many researchers found that lithium (Li) doping plays an important role in the inhibition of activity in the TiO 2 network acting as an electron trapping or hole trapping [239][240][241]. Bouattour et al reported Li-doped TiO 2 nanoparticles through a sol-gel process and investigated their potential application as a photocatalyst for degradation of different organic compounds [240].…”
Section: Other Metal Dopantsmentioning
confidence: 99%
“…51 Thus, RPA is increasingly used as a cost-efficient first-principles method for 4 modeling noncovalent interactions in molecules and materials. [52][53][54][55][56][57][58] Nevertheless, RPA underestimates dispersion energies 47 as a result of lacking higher excitations and density-driven error 59 inherited from the semilocal Kohn-Sham reference. The latter can be ameliorated by variational selfconsistent RPA 60 or perturbative singles corrections.…”
Section: Introductionmentioning
confidence: 99%
“…Previous experimental and theoretical works performed on TiO 2 bulk and surfaces clearly indicate that Li atoms can intercalate in the distorted octahedral cavities of TiO 2 with a charge transfer from the intercalated Li atom to a Ti site. As concerns in the theoretical studies, it is important to stress that pure DFT approaches fail to reproduce the electrochemical behavior of such systems due to the well-known self-interaction error found in pure LDA or GGA functionals, , contaminating the band gap and description of electron localization properties. Previous works have been indeed mainly performed with recurring molecular mechanics, HF, and DFT+U and more recently, hybrid DFT , methods, as done here. The electrochemical insertion process can be schematically described as indicated by the following equation where x is the mole fraction of lithium into TiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows the three most stable positions found for a neutral interstitial Li atom (Li i ) at the TiO 2 –LiKCO 3 interface: Li 1 corresponds to the most stable top-surface adsorption site, while Li 2 and Li 3 are two different subsurface configurations. Since cavities in deeper surface layers were already found to behave like bulklike layers where Li intercalation is less favorable, these insertion sites were not considered. Analogous configurations were also identified for the clean TiO 2 -(101) surface.…”
Section: Resultsmentioning
confidence: 99%